Baby-Boomers and the Romanian Financial System - Tudor Ciumara (Hyperion Economic Journal, 2014)
This paper analyses the possible contribution of the over-represented “decree” generation of the 1960’s and 1970’s to the development of the Romanian financial system. Contrary to most other studies on the subject, the focus of this paper is on the financial impact this generation can have before reaching retirement age. Consequently, the analysis is centered on the interaction between the members of this generation and the local financial institutions in the next two decades. It is suggested that the time frame used for this study is better suited for the strategic analysis requirements of financial institutions. It is argued that this generation is maturing professionally and moving towards reaching its financial peak in terms of individual earnings. Therefore, one of the main conclusions of the paper is that financial institutions should adjust their strategies in order to benefit from a significant opportunity